Vintage effects in human capital: Europe versus the United States - Robert Inklaar; Marianna Papakonstantinou (Luxembourg Income Study (LIS), 2017)
The standard assumption in growth accounting is that an hour worked by a worker of given type delivers a constant quantity of labor services over time. This assumption may be violated due to vintage effects, which were shown to be important in the United States since the early 1980s, leading to an underestimation of the growth of labor input (Bowlus and Robinson, 2012). We apply their method for identifying vintage effects to a comparison between the United States and six European countries. We find that vintage effects led to increases of labor services per hour worked by high-skilled workers in the United States and United Kingdom and decreases in Continental European countries between 1995 and 2005. Rather than productivity growth advantage of the US and UK, the primary difference with Continental European countries was human capital vintage effects instead.
Keywords: 330